2000
DOI: 10.1017/s0022112000001592
|View full text |Cite
|
Sign up to set email alerts
|

Highly turbulent Couette–Taylor bubbly flow patterns

Abstract: We present the results of experimental study of a Couette–Taylor system with superimposed axial flow and an upper free surface, in the high Taylor number regime. At large Taylor numbers, when the rotational speed of the inner cylinder increases, bubbles created near the free surface are distributed throughout the test section and permit the study of the spatial and temporal properties of turbulent flows using visualization techniques. In addition to classic travelling Taylor vortices, intermittent pulses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 18 publications
4
29
1
Order By: Relevance
“…In the present experiment, the breakup or coalescence of the bubbles does not occur. Also, trapping phenomena observed in the literatures (Climent et al, 2007, andAtkhen et al, 2000) was not observed in the present experiment. The effects of the accumulation are possibly smaller with respect to the buoyancy effects because the diameter of the bubbles of D = 4.7 mm is larger than those of the literatures, where the mean floating velocity ≈ 0.25 m/s is higher than the rotating speed of about 0.14 m/s.…”
Section: Relationship Between Position Of Aeration and Time For Floatcontrasting
confidence: 52%
“…In the present experiment, the breakup or coalescence of the bubbles does not occur. Also, trapping phenomena observed in the literatures (Climent et al, 2007, andAtkhen et al, 2000) was not observed in the present experiment. The effects of the accumulation are possibly smaller with respect to the buoyancy effects because the diameter of the bubbles of D = 4.7 mm is larger than those of the literatures, where the mean floating velocity ≈ 0.25 m/s is higher than the rotating speed of about 0.14 m/s.…”
Section: Relationship Between Position Of Aeration and Time For Floatcontrasting
confidence: 52%
“…However, the wall bubbles are found only in the outflow regions along the inner cylinder (shown by P4 in Figure 2), while positions denoted by P1, P2 and P3 are not favored. This may be attributed to the fact that pressure dominates among the various forces on the bubble [1], and P4 corresponds to the lowest pressure according to the pressure distribution calculated by Atkhen et al [4] 3.1 Core bubbles When bubbles of the same size are injected into a certain vortex core, a bubble ring forms at the center of the vortex such that bubbles are azimuthally uniformly distributed. Figure 3 shows a picture of a ring consisting of 61 bubbles.…”
Section: Resultsmentioning
confidence: 99%
“…Djeridi et al reported bubble capture and migration in a Couette-Taylor flow [3]. Atkhen et al presented an experimental study on the highly turbulent Couette-Taylor bubbly flow patterns [4]. Djeridi et al studied the mutual interactions between dispersed and continuous phases in the CouetteTaylor flow [5].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike what was seen for a lighter liquid dispersed in a heavier continuous phase where droplets tended to go toward the vortex cores, it has been shown that bubbles migrate toward the inner cylinder and are most stably located in rings along the regions of outflow between toroidal TC vortices [154][155][156][157]. Numerical studies have also been able to predict this behavior [154,158,159]. Batten et al [160] developed a method of using the average bubble distribution to identify the location of Taylor cells.…”
Section: Gas-liquid Dispersion Due To the Annular Region Beingmentioning
confidence: 99%
“…Atkhen et al [154] have observed the fluid mechanics of an annular contactor apparatus with radial vanes beneath the rotor directing the flow toward a downward axial exit (see also [149,162]). The device used in this work had a very long aspect ratio (total height relative to annular gap)-hydrodynamic observations were made with a liquid height of ∼50 cm and annular gaps of 5 mm and 10 mm.…”
Section: Gas-liquid Dispersion Due To the Annular Region Beingmentioning
confidence: 99%